النظائر المخادعة بين اللغة العربية واللغة الجاوية في تفسير الإبريز الجاوي - Hajiroh; Syirojul Huda (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2019)
ABSTRACT The aim of this study was to know the meaning of the homonym between Arabic and Javanese from surah Al-Fatihah to Surah Al-Baqarah verse 1-25 to encourage the Javanesse to learn Arabic and to learn Arabic and to convince was a difficult thing, as well as to make Arabic learning easier by showing them the function of this homonym. The method of this study as: the descriptive analytical method for comparing between Arabic and Javanese. The result from this study showed that there were homonym between the two languages. And from these words there were some words had the complete similarity between to phonems and some words had lack similarity between two phonems, but the words with lack similarity were much more. This study also showed that there was an effective method to learn Arabic and how to apply the fuction of the homonym from the beginners of Javanese speaking students by putting these homonyms in conversation, discourse, and the exercise. The most Important result of this study were: there were difference and similarity in the two language from Arabic and Javanese, and every words had a different meaning.